Risk factors associated with the persistence of human papillomavirus after cervical excision in patients with high-grade squamous intra-epithelial neoplasia. (November 2021) - Zang, Lejing; Huang, Jiahe; Zhu, Jufan; Hu, Yan
Abstract: Objective: To evaluate risk factors associated with the persistence of human papillomavirus (HPV) after cervical excision in patients with high-grade squamous intra-epithelial neoplasia (HSIL). Methods: A retrospective cohort study enrolled 550 patients who underwent cervical excision for HSIL between January 2015 and January 2018. The effects of various factors were assessed using univariate and multi-variate analyses. Results: The mean age of patients was 42.6 [standard deviation (SD) 8.7, range 22–64] years, and the mean duration of follow-up was 29.0 (SD 4.8, range 24–36) months. Persistent HPV infection after cone excision was detected in 78 (14.2%) patients. Univariate logistic regression analysis revealed that advanced age (>35 years), menopausal status, HPV type (HPV16/18), abnormal vaginal micro-ecological morphology, type of excision (loop electrosurgical excision procedure) and positive margin were closely associated with the persistence of HPV. Multi-variate analysis indicated that menopausal status [odds ratio (OR) 4.708, 95% confidence interval (CI) 2.770–8.001; p < 0.001], abnormal vaginal micro-ecological morphology (OR 2.320, 95% CI 1.372–3.922; p = 0.002) and positive margin (OR 3.346, 95% CI 1.261–8.876; p = 0.015) were significant risk factors for the persistence of HPV after treatment. Furthermore, infection with HPV16/18 increased the risk of persistent infection, and a higher rate of HPV persistence was found in patients who were infected with HPV18 (OR 1.020, 95% CI 0.415–2.505) or co-infected with HPV16/18 (OR 2.064, 95% CI 0.272–2.041) compared with HPV16. Conclusion: Persistent HPV infection after surgical treatment for HSIL is considered to be strictly related to the recurrence and progression of disease. Patients who are at increased risk of HPV persistence should receive intensive follow-up after surgery, especially in the first year.